Mapping of postoperative nursing care of cardiac surgery patients - Araújo, Wanessa Morais de (2012)
Descriptive study with quantitative approach that aimed to identify the care provided by nurses in intensive care unit for postoperative cardiac surgery patients and compare it to what is evidenced in the literature. The study was conducted in a large size university hospital located in Brazil, from January to February 2012. Six nurses completed the questionnaire containing questions on the socio-demographic profile and the care provided to postoperative cardiac surgery patients. The nursing cares identified were grouped into seven categories: maintenance of cardiac output, of tissue integrity, of electrolyte balance, of ventilation and oxygenation, prevention and treatment of pain, prevention and infection control, and psychological support. We conclude that the nursing actions identified in this study are consistent with the various practices recommended in the literature.